PERANCANGAN SISTEM INFORMASI INVENTORY BARANG JADI BERBASIS WEBSITE DENGAN METODE RAPID APPLICATION DEVELOPMENT (RAD) (STUDI KASUS: PT.INDORIS PRINTINGDO) - Retno Wulandari; Entis Sutrisna (CV. Multi Kreasi Media, 2023)
Inventory system is a system to find out the stock of an item in one place. Good inventory management is one of the determinants of the success of a manufacturing company. PT.Indoris Printingdo is a company engaged in the packaging industry which currently does not have an information system to manage all inventory data such as data storage of goods, finished goods and goods out, in the running system the production section provides reports finish goods in the form of paper to the warehouse so that recorded in Microsoft Excel, it takes a long time to search for data which is done manually by opening an excel file in each worksheet (sheet by sheet), resulting in delays in delivering information to the leadership and also to related parts. Therefore, a website-based information and inventory system was designed using the Rapid Application Development method. This information and inventory system is designed to be able to assist the operation of inventory, which aims to guarantee the right data source, the right quantity, and the right time, in which the data for finished or out goods will be automatically updated on the system. Storage, with the information system is expected to be able to increase the efficiency and effectiveness of inventory activities.